KONTESTASI DAN REPRODUKSI RUANG: NEGOISASI MASYARAKAT LOKAL MALINO DI TENGAH HEGEMONI KAPITALISME PARIWISATA - Amanda Sagita Putri; Sopian Tamrin; Idham Irwansyah Idrus (Yayasan Literasi Sains Indonesia, 2026)
The expansion of tourism development in Malino Subdistrict, Tinggimoncong District, Gowa Regency, has driven significant changes in the structure and function of space. The construction of villas, accommodations, and new tourist destinations has not only increased economic activity but has also triggered the conversion of agricultural land and green spaces into commercial areas. This study aims to analyze the dynamics of spatial production and reproduction resulting from tourism expansion, as well as the position of local communities within these changes. The research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving local residents, traders, and tourism workers. The data were thematically analyzed and interpreted using David Harvey’s three-dimensional spatial framework, namely absolute space, relative space, and relational space.The findings indicate that tourism expansion in Malino is dominated by capital forces that transform patterns of spatial ownership and utilization, leading to socio-economic inequality and environmental degradation. Within this context, local communities develop spatial reproduction strategies as forms of adaptation and negotiation, including the transformation of residential spaces into economic spaces (such as homestays, food stalls, and tourism services), shifts in livelihoods toward the informal tourism sector, the formation of kinship-based cooperation, and the strengthening of social networks with tourism actors and capital owners. These strategies demonstrate that local communities actively reproduce their living spaces to maintain access, social identity, and livelihood sustainability amid the dominance of capital in Malino’s tourism development.